2015
DOI: 10.1002/qj.2646
|View full text |Cite
|
Sign up to set email alerts
|

Simulating boundary‐layer rolls with a numerical weather prediction model

Abstract: Boundary‐layer rolls have an impact on bushfires, pollution dispersion, the triggering of extreme convective weather events, the air–sea interaction and intensification of tropical cyclones and momentum, particle and gas fluxes. Previous numerical modelling studies that investigate the effects of boundary‐layer rolls and the processes that control their dynamics have relied upon high‐resolution, idealised simulations. Recently, however, numerical weather prediction (NWP) systems have increased in horizontal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 69 publications
2
23
0
Order By: Relevance
“…The cold front associated with this low pressure passed Sweden on 2 May, bringing in colder air. Data from ground stations maintained by SMHI (Swedish Meteorological Institute) showed that the daily maximum temperature on the mainland was [15][16][17][18][19] ∘ C on 2 May and 10-14 ∘ C on 3 May. SST charts acquired from SMHI showed a temperature of [4][5] ∘ C in the parts of the Baltic Sea which will be studied here.…”
Section: Meteorological Conditions During Casesmentioning
confidence: 88%
See 4 more Smart Citations
“…The cold front associated with this low pressure passed Sweden on 2 May, bringing in colder air. Data from ground stations maintained by SMHI (Swedish Meteorological Institute) showed that the daily maximum temperature on the mainland was [15][16][17][18][19] ∘ C on 2 May and 10-14 ∘ C on 3 May. SST charts acquired from SMHI showed a temperature of [4][5] ∘ C in the parts of the Baltic Sea which will be studied here.…”
Section: Meteorological Conditions During Casesmentioning
confidence: 88%
“…Because the wind direction was southerly in the earlier part of the day it took a while before the rolls were advected out over the sea. During the time of full rolls the wavelength and amplitude did not change to a large degree, which justified using a time average, in contrast to, for example, the study by Thurston et al [19]. After the rolls started dissipating in the evening, there was a gradual transition until they completely disappeared.…”
Section: Boundary Layer Roll Characteristics From Sar Imagesmentioning
confidence: 90%
See 3 more Smart Citations